Experimental Investigation into the Exergy Loss of a Ground Heat Pump and its Optimization Based on Approximation of Piecewise Linear Functions - Osintsev, K. V.; Alyukov, S. V. (Journal of engineering physics and thermophysics, 2022)
The authors have presented experimental data on determining the thermodynamic parameters of a ground heat pump operating on Freon R407c on whose basis the exergy of the flow and the exergy loss in structural elements were calculated. A methodological approach to implementing the exergetic method of thermodynamic analysis has been developed on the basis of novel techniques of approximation of piecewise linear functions. An example of calculation of a ground heat pump operating on Freon R407c with account taken of the exergy of flows in it and their exergetic temperature, and also of the coefficient of performance COP of the pump has been given. The developed methodology can be used in designing novel types of low-temperature power plants: refrigerating machines, heat pumps, thermotransformers, and the organic Rankine cycle operating on new refrigerants, also on zeotropic and azeotropic mixtures.